CDH6 as a prognostic indicator and marker for chemotherapy in gliomas - Meng, Ming; Zhou, Hongshu; He, Ye; Chen, Lu; Wang, Wanpeng; Yang, Liting; Wang, Zeyu; Zhang, Liyang; Wang, Sha (Frontiers in Genetics, 2022)
Glioma is the most malignant cancer in the central nervous system. There are various therapies for glioma but treating effects remain poor. New targets for glioma treatment are needed. The current study examined CDH6 expression in TCGA and CGGA glioma datasets. CDH6 expression was found to be positively correlated with WHO grade and negatively correlated with patient prognosis. A significant decrease of CDH6 promoter methylation was then identified with the increase in WHO Grade. GO and KEGG enrichment analyses suggested CDH6 might be involved in cell-cell interactions and immune processes in glioma microenvironment. WGCNA analysis identified CDH6 to be correlated with cell adhesion molecules, focal adhesions, PI3K-Akt signaling pathways, nuclear division, chromosome segregation, mitotic nuclear division, and immune-related pathways. CDH6 showed strong correlations with immune suppressive cells including Tregs, monocytes, macrophages, TAMs, MDSCs. It also showed correlations with immune active cells like B cells, CD8+ T cells, and DCs. Single cell analysis identified that CDH6 was expressed mainly in astrocyte (AC)-like malignant cells. Differentially expressed genes of AC-like malignant cells were found to be associated with stress response, membranous processes, virus infection, and several types of cancers. Potential drugs for high CDH6 expression were also predicted including AMG-22, rutin, CCT128930, deforolimus, bis(maltolato)oxovanadium, anagrelide, vemurafenib, CHIR-98014, and AZD5582. We therefore report CDH6 is correlated with glioma immune infiltration, is expressed mainly in astrocyte-like malignant cells, and may act as a new target for glioma therapy.